Solving large scale learning tasks : challenges and algorithms : essays dedicated to Katharina Morik on the occasion of her 60th birthday /: challenges and algorithms : essays dedicated to Katharina Morik on the occasion of her 60th birthday. (2016) - Unknown
No abstract available